Налоговые стимулы НИОКР в условиях эмерджентной экономики: направление реформ для Украины - Мазур, Ю.А. (Економіка промисловості, 2017)
Статья посвящена обоснованию целесообразности использования налоговых стимулов НИОКР для инновационного развития промышленных предприятий Украины. Рассмотрены преимущества и недостатки использования инвестиционных налоговых кредитов в сфере НИОКР в условиях эмерджентной экономики. Выявлены особенности использования объемной и приростной схемы квалифицированных расходов (доходов) при исчислении инвестиционного налогового кредита в сфере НИОКР в разных странах мира. Установлено, что в развивающихся странах наиболее подходящим является использование объемного инвестиционного налогового кредита в связи с тем, что он является простым для использования предприятиями и для администрирования государством. Предложен усовершенствованный эволюционный подход к налоговому стимулированию НИОКР, который направлен на исследование налогового стимулирования промышленных предприятий в условиях предоставления им объёмного налогового кредита в сфере НИОКР. Установлено, что применение налоговых стимулов в сфере НИОКР может способствовать росту инвестиционной активности предприятий и ускорению их инновационного развития. Ограниченность бюджетного финансирования промышленности в стране может быть компенсирована, по крайней мере частично, при помощи такого инструмента налоговой политики, как объёмный инвестиционный налоговый кредит. Статтю присвячено обґрунтуванню доцільності використання податкових стимулів НДДКР для інноваційного розвитку промислових підприємств України. Розглянуто переваги та недоліки використання інвестиційних податкових кредитів у сфері НДДКР в умовах емерджентної економіки. Виявлено особливості використання об'ємної та прирісної схеми кваліфікованих витрат (доходів) при обчисленні інвестиційного податкового кредиту у сфері НДДКР у різних країнах світу. Встановлено, що в країнах, які розвиваються, найбільш доцільним є використання об'ємного інвестиційного податкового кредиту у зв'язку з тим, що він є простим для використання підпри-ємствами та для адміністрування державою. Запропоновано вдосконалений еволюційний підхід до оцінки податкового стимулювання НДДКР, із використанням якого досліджено стимулювання промислових підприємств в умовах надання їм об'ємного податкового кредиту у сфері НДДКР. Встановлено, що застосування податкових стимулів у сфері НДДКР може сприяти зростанню інвестиційної активності підприємств і прискоренню їх інноваційного розвитку. Обмеженість бюджетного фінансування промисловості в країні може бути компенсована, принаймні частково, за допомогою такого інструменту податкової політики, як об'ємний інвестиційний податковий кредит. One of the main features of tax incentives for R&D is the creation of certain benefits for society in general and industry enterprises in particular. This is achieved by attracting additional investments for the development of the innovative sphere of the economy. International practice confirms the effectiveness of tax mechanisms for stimulating R&D both in advanced economies and in those economies that are developing and considered as emergent. Governments use these mechanisms both as a tool to support broad R&D and as a targeted public policy to foster innovation in specific fields. The article is devoted to the justification of the expediency of using tax incentives for research and development for the innovative development of industrial enterprises in Ukraine.The features of using the investment tax credits in the sphere of research and development in the conditions of the emergent economy are considered including the ease of implementation, attraction of the private investments, reducing the effective tax burden on businesses and so on. The main requirement of R&D investment tax credit should be the activity in the sphere of the scientific and technological progress.The features of using the volume and incremental scheme of qualified expenses (income) in calculating the tax credit for investment in R&D in different countries of the world are identified. It was determined that the volume tax credit for investment in R&D is more appropriate for applying in developing countries because it is simple to use by enterprises and to administrate by state and it contributes to the growth of profits of large enterprises, and, consequently, increases investment in research and development. In contrast to the incremental scheme aimed mainly at stimulating the small and medium-sized businesses, tax incentives for large enterprises by means of the volume tax credit for investment in R&D is a more effective tool for ensuring stable GDP growth rates in the conditions of socio-economic crisis.The improved evolutionary approach to tax incentives for R&D is proposed. It is aimed at researching the tax incentives for industrial enterprises in the context of providing them with a volume tax credit for investment in R&D. It was determined that the application of tax incentives in the field of research and development can contribute to the growth of investment activity of enterprises and to accelerate their innovative development. The limited budget financing of industry in the country can be compensated, at least in part, with the help of such a tax policy tool as a volume tax credit for investment in R&D.